2013
DOI: 10.4322/floram.2013.044
|View full text |Cite
|
Sign up to set email alerts
|

Uso de Espécies da Flora na Comunidade Rural Santo Antônio, BR-163, Amazônia Brasileira

Abstract: Realizou-se um estudo etnobotânico por meio de entrevistas com agricultores familiares da Comunidade Santo Antônio, localizada no Assentamento Moju I e II, região do entorno da rodovia BR-163. Foram encontradas 55 etnoespécies, sendo 67,3% nativas e 58,2% de porte arbóreo. O Índice de Diversidade de espécies (H') foi 2,83 para espécies exóticas, 3,44 para nativas e 3,77 para o agrupamento. A similaridade entre espécies da floresta manejada e as etnoespécies foi de 18%. A floresta manejada oferece 51,4% das esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…In 2016, diarrhea was the main cause of hospitalizations in the health system in the Research, Society and Development, v. 11, n. 1, e56911125258, 2022(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i1.25258 municipality of Belém (IBGE, 2016. Ethnobotanical studies undertaken in other rural Brazilian communities likewise reported high frequencies of those same infirmities (Cunha & Bortolotto, 2011;Almeida, et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In 2016, diarrhea was the main cause of hospitalizations in the health system in the Research, Society and Development, v. 11, n. 1, e56911125258, 2022(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i1.25258 municipality of Belém (IBGE, 2016. Ethnobotanical studies undertaken in other rural Brazilian communities likewise reported high frequencies of those same infirmities (Cunha & Bortolotto, 2011;Almeida, et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…One of the principal characteristics of rural settlements in the Amazon region has been their role in maintaining the Legal Reserve Forests required by Brazilian legislation (Cunha & Bortolotto, 2011). They also have potential for developing agro-extractivism projects that would lend value to Amazonian medicinal plants and foster the diversification of the economic activities of those rural groups (De Almeida, et al, 2013). Within that context, the present ethnobotanical study undertaken in the Paulo Fonteles Settlement Lands (APF), located in the Mosqueiro district (Belém, Pará State), sought to elucidate the roles of medicinal plants in local therapeutic practices and identify species of potential value to official health services.…”
Section: Introductionmentioning
confidence: 99%
“…Na Amazônia brasileira, pesquisas etnobotânicas com moradores de áreas urbanas, como nos estudos de Emperaire e Eloy (2008) e Siviero et al (2011), constataram a importância dos quintais agroflorestais como espaços para manutenção de espécies e variedades produtoras de recursos alimentares, constituindo um estreitamento da relação entre comunidades florestais e áreas urbanas. Em comunidades rurais, estudos revelam a importância em conhecer o saber popular para a criação de programas de conservação da diversidade e geração de renda, bem como a preservação do conhecimento popular (Almeida et al, 2013;SALTOS et al, 2016).…”
Section: Introductionunclassified
“…Existe uma gama de árvores, arbustos, ervas e cipós que contribuem, em diversos âmbitos, para o modo de vida das populações Amazônicas [7]. Assim, devido às influências culturais, essas comunidades humanas detêm a prática e o conhecimento para se utilizar vegetais, porém esse saber esta em erosão devido a perda das características rurais de vários ambientes, assim a etnobotânica assume o papel de resgatar esse conhecimento [8].…”
Section: Introductionunclassified